Guideline for oral care of dependent elders: mapping review and cross-cultural adaptation to Portuguese-Brazil - Rafaella Mendes de JESUS; Fernanda Lamounier CAMPOS; Lorrany Gabriela RODRIGUES; Matheus de França PERAZZO; Anna Rachel dos Santos SOARES; Marco Túlio de Freitas RIBEIRO; Aline Araújo SAMPAIO; Raquel Conceição FERREIRA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study aimed to map evidence-based guidelines for oral care of the dependent elders and perform the cross-cultural adaptation to Brazilian Portuguese. Initially, a systematized review was conducted in Medline, Scielo, Scopus, Web of Science, and Google Scholar databases without restrictions in search period or type of study. Articles in English, Spanish, and Brazilian Portuguese describing evidence-based guidelines for oral care, including oral hygiene recommendations, of institutionalized dependent elders were included as long as they presented an evaluation of evident quality. The guideline that met inclusion criteria was submitted to cross-cultural adaptation after obtaining permission from the original authors. Two hundred and nineteen references were found. Three selected articles described evidence-based guidelines for oral care, but the Oral Health Care Guideline for Older People in Long-term Care Institutions (OGOLI), originally developed and implemented in the Netherlands, was selected. It was based on evidence level A2 and consensus of experts and met the quality requirements of the Appraisal of Guidelines for Research & Evaluation (AGREE). This guideline presents oral care recommendations for elders with different levels of dependence in activities of daily living to be performed by caregivers and nursing staff. The adaptation of the OGOLI was mainly on the attributions of care providers, given the differences in professional regulations between Brazil and the Netherlands. The cross-cultural equivalence between OGOLI and its Brazilian Portuguese version was verified.